English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

(x^6)-(x^2)

show / explain to me the steps

2007-06-18 07:10:27 · 4 answers · asked by yo 2 in Science & Mathematics Mathematics

OR HOW WOULD YOU SIMPLIFY THE EXPRESSION, IS WHAT I MEANT

2007-06-18 07:17:02 · update #1

4 answers

it is already simplified as far as you can.

2007-06-18 07:19:28 · answer #1 · answered by derekk07 2 · 0 0

Do you want to solve it or factorise it?
If you want to factorise it,here is the answer
(x^6)-(x^2)
=x^2(x^4-1)
=x^2{(x^2)^2-(1)^2}
=x^2(x^2+1)(x^2-1)
=x^2(x^2+1){(x)^2-(1)^2}
=x^2(x^2+1)(x+1)(x-1)
If however you want to solve it,you may take the help of above factors to find the values of x ,if x^6-x^2=0

2007-06-18 14:16:37 · answer #2 · answered by alpha 7 · 0 0

Solve it for what? Since it is not equal to anything, it is hard to solve it for something. It is simply x to the sixth power minus x to the second power. It can give you a set of answers if x = a number, but that is about it.

2007-06-18 14:14:44 · answer #3 · answered by Mark S 3 · 0 0

=x^2(x^4-1)=x^2(x^2-1)(x^2+1)= x^2(x-1)(x+1)(x^2+1)
The last factor,in complexd numbers can be written as
(x-i)(x+i) where i^2=-1

2007-06-18 14:21:24 · answer #4 · answered by santmann2002 7 · 0 0

fedest.com, questions and answers